Effects of dietary copper intake on blood lipids in women of childbearing age and the potential role of gut microbiota - Luo, Mingming; Guo, Linmei; Wu, Chunmei; Hao, Ming; Gu, Junwang; Li, Xuhuan; Wang, Qi (Frontiers in Nutrition, 2024)
Background: Copper (Cu) is a vital trace element involved in numerous physiological processes, including glycolysis and lipid metabolism. Imbalances in Cu homeostasis can contribute to various diseases. However, current research on the impact of Cu on lipid metabolism has yielded inconsistent findings. Moreover, studies investigating the effects of dietary Cu intake on blood lipids among women of childbearing age are rare.Understanding of this relationship could enhance lipid management, given that most women obtain Cu through their diet. Additionally, the gut microbiota may play a role in this process. This study aims to investigate the effects of dietary Cu intake on blood lipids in women of childbearing age and to analyze the role of gut microbiota in this process.Methods: This study utilized data from the National Health and Nutrition Examination Survey (NHANES) to conduct a preliminary analysis of the correlation between dietary Cu levels and blood lipid indicators in women of childbearing age. Subsequently, an on-site research was conducted to further investigate this relationship, followed by animal experiments to verify the effect of different Cu doses on blood lipid levels.Multiple linear regression models, ANOVA, XGBOOST were employed to analyze the impact of Cu on blood lipids and the role of intestinal microbiota in this process.In the population study, the NHANES results were consistent with on-site findings. The TG, and TC levels in women with childbearing were increased with higher dietary Cu intake. Animal experiments have shown that as Cu intake increases, TC levels increase. Furthermore, when the Cu intake reached 8mg/day (the recommended dietary Cu intake limit of China, RDI), the TG levels in the research animals decrease, alongside a reduction in the abundance of Weissella cibaria (probiotics related to lipid metabolism), and the levels of LPS and IL-6 increase.The blood lipid levels of women of childbearing age increase with higher dietary Cu intake. RDI of 8mg/day for women of childbearing age in China may need to be appropriately reduced. Regulating the gut microbiota, especially by increasing the abundance of Weissella cibaria may be an effective intervention for blood lipids.